Pembelajaran Berbasis Karakter Nilai - Abduloh Abduloh (Universitas Mathla'ul Anwar Banten, 2020)
This paper seeks to describe the concept of implementation and learning outcomes based on character values ​​as an effort to achieve the goals to be achieved by an individual / community group in order to improve lives in the present and the future effective and efficient, so it needs a variety of support resources that must be met so that learning can be implemented optimally. This study uses a concept analysis method of Character-Based Learning Values